2022
DOI: 10.1177/15357597221086111
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Focused Ultrasound for Epilepsy— A New Approach to Neuromodulation

Abstract: Patients with drug-resistant epilepsy (DRE) who are not surgical candidates have unacceptably few treatment options. Benefits of implanted electrostimulatory devices are still largely palliative, and many patients are not eligible to receive them. A new form of neuromodulation, low intensity focused ultrasound (LIFUS), is rapidly emerging, and has many potential intracranial applications. LIFUS can noninvasively target tissue with a spatial distribution of highly focused acoustic energy that ensures a therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Focus ultrasound includes two main therapeutic mechanisms: thermal ablation of epileptogenic regions using high-intensity focus ultrasound (HIFU) or, neuromodulation of epileptogenic networks using lowintensity focus ultrasound (LIFU). Several preclinical studies have demonstrated that focus ultrasound can ablate or suppress epileptiform activity in animal epilepsy models [51]. Two anecdotal case reports have been published showing improvement in seizure control after HIFU tissue ablation in patients with hypothalamic hamartoma [52,53].…”
Section: Advancements In Minimally Invasive Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus ultrasound includes two main therapeutic mechanisms: thermal ablation of epileptogenic regions using high-intensity focus ultrasound (HIFU) or, neuromodulation of epileptogenic networks using lowintensity focus ultrasound (LIFU). Several preclinical studies have demonstrated that focus ultrasound can ablate or suppress epileptiform activity in animal epilepsy models [51]. Two anecdotal case reports have been published showing improvement in seizure control after HIFU tissue ablation in patients with hypothalamic hamartoma [52,53].…”
Section: Advancements In Minimally Invasive Proceduresmentioning
confidence: 99%
“…Two anecdotal case reports have been published showing improvement in seizure control after HIFU tissue ablation in patients with hypothalamic hamartoma [52,53]. Moreover, several human pilot studies have shown that LIFU is able to elicit cortical modulatory effects in several brain regions [51], with some studies showing alteration of EEG oscillations following LIFU [54]. A recent report has demonstrated that LIFU in presurgical patients with TLE resulted in no histological signs of tissue damage to the resected mesial temporal structures [55], conveying a well tolerated profile to LIFU for neuromodulation in DRE.…”
Section: Advancements In Minimally Invasive Proceduresmentioning
confidence: 99%
“…High-intensity FUS (~1000 W/cm 2 ) execute the thermoablation effect, while low-intensity mode (~3 W/cm 2 ) showed neuromodulatory effects and suppressive effects on the frequency of epileptic signal bursts. The proposed mechanism of action of low-intensity FUS included the following [78]:…”
Section: Focused Usgmentioning
confidence: 99%
“…There are ongoing clinical trials testing the efficacy of TUS for the treatment of drug-resistant epilepsy [45], after its safety has been established in animal models. In a penicillin-induced epilepsy model in two non-human primates, offline TUS decreased the seizure frequency and duration in both macaques for up to seven hours after TUS [46].…”
Section: Clinical Applicationsmentioning
confidence: 99%